The Effect of Substitution of Buffalow Milk with Soy Milk on the Nutritional Value of Palopo - Marhama Marhama; Satrijo Saloko; Siska Cicilia (Journal of Food and Agricultural Product, 2022)
This study aims to determine the nutritional value of palopo which was substituted with soy milk. This study used an experimental method with a one-factor completely randomized design (CRD) consisting of 6 levels of ratio of buffalo milk: soy milk, namely K0 = 100%: 0%, K1 = 80%: 20%, K2 = 60%: 40%. , K3 = 40%: 60%, K4 = 20%: 80% and K5 = 0%: 100% with 3 repetitions. The observed data were analyzed for variance (Analysis of Variance) with a real level of 5%. If there is a significant difference, a 5% BNJ further test is performed. The parameters observed in this study were fat content, protein content, moisture content, antioxidant activity, total phenol, and sensory parameters including aroma and taste. The results showed that there was a significant effect on all observed parameters but had an insignificant effect on oHue. The higher the ratio of soy milk causes an increase in antioxidant activity, water content, total phenol but decreases fat content, protein content and viscosity of palopo. In terms of chemical, physical and sensory parameters, the treatment with a ratio of 80% buffalo milk: 20% soy milk was the best result with an antioxidant activity value of 50,50%; total phenol 4,58 mg GAE / g; water content 71,39%; fat content 5,23%; protein content 3,54%; and sensory quality that can be accepted by the panelists. Keyword : buffalo milk, palopo, soy milk